Evaluation and Assessment of Aflatoxin M1 in Milk and Milk Products in Yemen Using High-Performance Liquid Chromatography - Safwan Murshed (Journal of Food Quality)
Aflatoxin M1 is one of the major fungal contaminants found in dairy products around the globe. The objective of this study was to investigate the incidence and occurrence of aflatoxin M1 (AFM1) in samples of milk and milk products in Yemen. The tested dairy product samples were collected from different sources for aflatoxin M1 (AFM1) in Yemen. A total of 250 local and imported samples consisting of 38 liquid milk, 60 powder milk, 62 yogurt, and 90 cheese samples which are marketed throughout Yemen were tested by using high-performance liquid chromatography (HPLC) along with a fluorescence detector and immunoaffinity column purification for detection of AFM1. High levels of AFM1 were detected in preserved milk (77.24%), ranging from 0.021 μg/L to 5.95 μg/L. On the other hand, AFM1 was detected in 66.66% and 68.42% in powdered milk and liquid milk samples, respectively. Among dairy products, 87.09% of yogurt and 81.39% of cheese samples were found contaminated with AFM1. The AMF1 values were higher than the acceptable range for humans set by the European Union. So, we concluded that dairy products used in Yemen showed an AFM1 content beyond the acceptable range, and this is a major factor for causing health-related complications including cancer. In the present study, we reported for the first time the presence of mycotoxins especially AFM1 in dairy products used in Yemen.